Happy silly birthday to me - McGovern, Ann.; Dreamer, Sue (New York : Scholastic, 1994)
A story in rhyme about having silly birthday parties with clowns and elephants, goblins and ghosts, in an elevator, on a pirate ship, on a jungle floor, in a firehouse, and so on.
"Cartwheel Books."
K-3
Keywords: Birthdays -- Fiction; Stories in rhyme; Birthdays -- Fiction; Stories in rhyme